Concordance study between the ParaDNA® Intelligence Test, a Rapid DNA profiling assay, and a conventional STR typing kit (AmpFlSTR® SGM Plus®). (May 2015) - Ball, G.; Dawnay, N.; Stafford-Allen, B.; Panasiuk, M.; Rendell, P.; Blackman, S.; Duxbury, N.; Wells, S.
Highlights: The ParaDNA Intelligence Test is a novel STR profiling kit for rapid DNA profiling. We analysed 381 individuals with ParaDNA Intelligence Test and AmpFlSTR SGM Plus. We describe the high level of concordance demonstrated between the two systems. 99.8% of ParaDNA Intelligence Test alleles were concordant with AmpFlSTR SGM Plus. The likelihood of an adventitious match was estimated at approximately 1 in 2.7 × 10 6 . Abstract: The ParaDNA ® Intelligence Test enables STR profiling directly from human biological samples and evidence items collected from crime scene in 75 min. Designed for non-expert use this system allows DNA information to be available to investigators before it would typically be available from a laboratory. The ParaDNA Intelligence Test system amplifies D3S1358, D8S119, D16S539, D18S1358 and TH01 STR loci and the gender typing locus amelogenin and detects the alleles present with HyBeacon ® probes. Individual DNA samples from 381 UK Caucasian individuals were analysed using AmpFlSTR ® SGM Plus ® and the ParaDNA Intelligence Test with the derived STR profiles compared. Here we describe the high level of concordance demonstrated between the two systems and discuss this with reference to allele frequencies and the discriminatory power offered by the ParaDNA Intelligence Test.